The effect of discounts, Ease of shopping, lifestyle, and price on online purchase decisions on the shopee marketplace (study of ITB Yadika Bangil students, faculty of law and business) - Agustina, Silvia Rudya; Churniawati, Ninik (Jurnal Mantik, 2024)
The proliferation of online stores makes the actors compete in terms of attracting customers. One way is to make discounts, the ease of online shopping offered, Millennial lifestyle trends and prices. This study uses a type of quantitative data, namely data obtained in the form of numbers obtained from the distribution of distributed questionnaires. Based on the data sources used in this study, primary and secondary data are used. Primary data is data obtained through a questionnaire given to ITB Yadika Pasuruan students. The results of the study showed that the variables of discount, ease of shopping, lifestyle partially had no significant effect on online purchase decisions. Meanwhile, price has a significant effect on online purchase decisions